The dynamics of attentional sampling during visual search revealed by Fourier analysis of periodic noise interference - Dugue, L.; VanRullen, R. (Journal of vision (Charlottesville, Va.), 2014)
What are the temporal dynamics of perceptual sampling during visual search tasks, and how do they differ between a difficult (or inefficient) and an easy (or efficient) task? Does attention focus intermittently on the stimuli, or are the stimuli processed continuously over time? We addressed these questions by way of a new paradigm using periodic fluctuations of stimulus information during a difficult (color-orientation conjunction) and an easy (+ among Ls) search task. On each stimulus, we applied a dynamic visual noise that oscillated at a given frequency (2-20 Hz, 2-Hz steps) and phase (four cardinal phase angles) for 500 ms. We estimated the dynamics of attentional sampling by computing an inverse Fourier transform on subjects' d-primes. In both tasks, the sampling function presented a significant peak at 2 Hz; we showed that this peak could be explained by nonperiodic search strategies such as increased sensitivity to stimulus onset and offset. Specifically in the difficult task, however, a second, higher-frequency peak was observed at 9 to 10 Hz, with a similar phase for all subjects; this isolated frequency component necessarily entails oscillatory attentional dynamics. In a second experiment, we presented difficult search arrays with dynamic noise that was modulated by the previously obtained grand-average attention sampling function or by its converse function (in both cases omitting the 2 Hz component to focus on genuine oscillatory dynamics). We verified that performance was higher in the latter than in the former case, even for subjects who had not participated in the first experiment. This study supports the idea of a periodic sampling of attention during a difficult search task. Although further experiments will be needed to extend these findings to other search tasks, the present report validates the usefulness of this novel paradigm for measuring the temporal dynamics of attention.